Numerical research on sloshing of free oil liquid surface based on different baffle shapes in rectangular fuel tank. (February 2020) - Zhang, Enhui
Oil liquid sloshing is a normal physical phenomenon in fuel tank under variable conditions of vehicles. Installing baffles in fuel tank is an effective method to suppress oil liquid sloshing. The influence of different baffle shapes on the pressure of oil liquid sloshing and time-area value is the focus of this work. Four factors influencing the baffle shape and baffles of six different shapes are provided in this research. The pressure history curves of oil liquid sloshing at the central point and on the central line, the history curves of velocity of oil liquid mass and volume, oil liquid pressure contours, and the position diagrams of free oil liquid surface were obtained and compared in fuel tanks with baffles of different shapes. Compared with the sloshing pressure of oil liquid and time-area values in fuel tanks with baffles of different shapes, the sloshing pressure of oil liquid at the central point is the smallest in fuel tank with baffles of corrugated shape, and the sloshing pressure of oil liquid on the central line is the smallest in fuel tank with baffles of straight-line shape. However, the baffles of corrugated shape are most beneficial to reduce time-area values.